A study of ethics and information technology usage among UUM international students / Abdul Manaf Bohari and Nurul Hafizan Mazani - Bohari, Abdul Manaf; Mazani, Nurul Hafizan (2010)
Basically, ethics is a universal of guiding beliefs, standards, or ideas that pervades an individual, a groupor community of people and individually is accountable for their actions and behaviors. The emerging ofworld wide ICT, ethics also are related to Information Technology (IT) and requires one to behaveethically rights. Ethics of IT users are varying among regions, cultures, and societies; and based onliterature review, it was depending on beliefs and perceptions. Currently, IT drastically changes the wayhow ethics will conduct and practiced within organizations. Therefore, the main objective of this researchis to identify what is perceived as ethical behavior regarding IT usage. Secondly, this research is to observethe ethics among international students in relation to IT. In order to conduct this research, questionnaireswill be used to collect the primary data from respondents, as well as international students of Universti.Utara Malaysia. The data collected will then be analyzed by using Statistical Package for Social Science (SPSS) software. As conclusion, ethics towards IT is varied among individual whereas from differs counties as well as Indonesia, Thailand, China, Iraq, and Pakistan and mostly, it is based on attitudes or perception in to what extent does it said to be ethical while dealing with IT.